Could Home Sexually Transmitted Infection Specimen Collection With e-Prescription Be a Cost-Effective Strategy for Clinical Trials and Clinical Care?. Issue 1 (January 2015) - Blake, Diane R.; Spielberg, Freya; Levy, Vivian; Lensing, Shelly; Wolff, Peter A.; Venkatasubramanian, Lalitha; Acevedo, Nincoshka; Padian, Nancy; Chattopadhyay, Ishita; Gaydos, Charlotte A.
<x xml:space="preserve">Abstract</x> Background Results of a recent demonstration project evaluating feasibility, acceptability, and cost of a Web-based sexually transmitted infection (STI) testing and e-prescription treatment program (eSTI) suggest that this approach could be a feasible alternative to clinic-based testing and treatment, but the results need to be confirmed by a randomized comparative effectiveness trial. Methods We modeled a decision tree comparing (1) cost of eSTI screening using a home collection kit and an e-prescription for uncomplicated treatment versus (2) hypothetical costs derived from the literature for referral to standard clinic-based STI screening and treatment. Primary outcome was number of STIs detected. Analyses were conducted from the clinical trial perspective and the health care system perspective. Results The eSTI strategy detected 75 infections, and the clinic referral strategy detected 45 infections. Total cost of eSTI was $94, 938 ($1266/STI detected) from the clinical trial perspective and $96, 088 ($1281/STI detected) from the health care system perspective. Total cost of clinic referral was $87, 367 ($1941/STI detected) from the clinical trial perspective and $71, 668 ($1593/STI detected) from the health care system perspective. Conclusions Results indicate that eSTI will likely be more cost-effective (lower cost/STI detected) than clinic-based STI screening, both in the context of clinical trials and in routine clinical care. Although our results are promising, they are based on a demonstration project and estimates from other small studies. A comparative effectiveness research trial is needed to determine actual cost and impact of the eSTI system on identification and treatment of new infections and prevention of their sequelae.